Influence of housing systems on duck behavior and welfare - Hamid, Shereen El Abdel; Saleem, Al Sadik Y; Youssef, Mohamed I; Mohammed, Hesham H; Abdelaty, Asmaa I (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This experiment was conducted to assess the effects of the housing system on the welfare and growth performance of the Muscovy duck. Materials and methods: A total number of 48 Muscovy duck aged 3-week old were divided randomly into two groups (24 duck on each): deep litter system and cage system. Each group was subdivided into three replicates (8 birds on each) were identified with wing rings. Results: The study showed that feeding and drinking behaviors significantly increased (p < 0.05) in duck reared at the cage system. While there was no noticeable effect on lying and feather pecking, duck raised in the deep litter had better growth performance with a substantial difference, which achieve a higher feed conversion rate with lower feed efficiency. Physical conditions were significantly better at cage management. The level of stress indicating hormones indicating free Thyroxin was increased with the cage. Therefore, the litter system improves duck welfare and their performance. Conclusion: It is concluded that the duck managed under the litter system has more opportunities that facilitate the expression of more natural behavior, and thus improve their health and performance, as a result of improved feed conversion rate and feed efficiency. J. Adv. Vet. Anim. Res., 7(3): 407-413, Sep 2020 http://doi.org/10.5455/javar.2020.g435